UN Desertification and Drought Day 2025: Linking soil health, gender equity, and sustainable land management - Ringler, Claudia; Kato, Edward; Kiguli, Geoffrey (International Food Policy Research Institute, 2025)
Healthy soils play a critical role in supporting agricultural productivity, climate change adaptation and mitigation, and a range of ecosystem services. Yet sub-Saharan Africa has experienced the most severe land degradation in the world.